Self-monitoring of blood glucose in noninsulin-treated type 2 diabetes: an overview - Nanne Kleefstra (Dove Medical Press, 2009)
Nanne Kleefstra1, Johanna Hortensius1, Kornelis JJ van Hateren1, Susan JJ Logtenberg1, Sebastiaan T Houweling2, Rijk OB Gans3, Henk JG Bilo11Diabetes Centre, Isala Clinics, Zwolle, The Netherlands; 2Langerhans Medical Research Group, The Netherlands; 3Department of Internal Medicine, University Medical Center Groningen, Groningen, The NetherlandsIntroduction: The effectiveness of self-monitoring of blood glucose (SMBG) in noninsulin-treated patients with type 2 diabetes (T2DM) remains unclear. We aimed to review the trials investigating the effects of SMBG in this population.Methods: Medline was searched until June 29, 2009. Randomized controlled trials (RCTs) of at least 12 weeks’ duration were included. Data on the following aspects were gathered: patient and study characteristics, effects on HbA1c, quality of life and treatment satisfaction, and methodological quality.Results: The search revealed 9 original RCTs. These studies were very heterogeneous, and 5 were classified as of high quality. The studies with the best methodology did not show an effect of SMBG on HbA1c, the studies with the worst methodological quality did. Two out of the 4 studies that assessed quality of life showed a significant change in favor of the control group, 1 study showed a significant change in favor of SMBG.Discussion and conclusion: We found an inverse relation between study quality and efficacy of SMBG. At this moment, there is no basis for general use of SMBG in noninsulin-treated T2DM patients.Keywords: blood glucose self-monitoring, diabetes mellitus, type 2, blood glucose, hemoglobin A, glycosylated